Mango Peel Pectin by Microwave-Assisted Extraction and Its Use as Fat Replacement in Dried Chinese Sausage - Malaiporn Wongkaew; Sarana Rose Sommano; Tibet Tangpao; Pornchai Rachtanapun; Kittisak Jantanasakulwong (Foods, 2020)
In this research, low-fat dried Chinese sausage was formulated with mango peel pectin (MPP; 0%, 5%, 10%, and 15% (w/w)) extracted by microwave assisted extraction (MAE). The extractable yield of pectin attained from peel of Nam Dok Mai variety was achieved at 13.85% using 700-watt power. The extracted MPP were of high equivalent weight (1485.78 mg/mol), degree esterification (77.19%) and methoxyl content (19.33%) with a structure of greater porosity as compared to that of the conventional method. Spectrum scans by Fourier transform infrared spectrophotometer (FT-IR) indicated that the extracted MPP gave similar wave number profiles as the commercial pectin. Quality attributes of the Chinese sausages were assessed and compared with the control formula (CTRL). At higher concentrations of MPP, the intensity of redness and yellowness in sausage increased. The texture profile of the sausage illustrated that only the hardness value was comparable with the CTRL, while springiness, cohesiveness, gumminess and chewiness were statistically lower (p < 0.05). Furthermore, the sensory evaluation by experienced panellists (n = 12) indicated that 5% MPP similarly represented overall acceptability with the CTRL. Consequently, MPP can be effectively incorporated in the formula at low level to replace fat in Chinese sausage, allowing colour improvement and production of a healthier option.